Shock Therapy! : What Role for Thai Monetary Policy? - Alp, Harun (IMF Working Papers; Working Paper ;, 2012)
Thailand had to endure three major shocks during 2008-2011: the global financial crisis, the Japanese earthquake, and the Thai floods of 2011. Over this period, consistent with its inflation targeting framework, the Bank of Thailand (BOT) let the exchange rate depreciate and cut interest rates (to, for example, a historically low level of 1u percent by mid-2009). This paper seeks to uncover the role of monetary policy in softening the impact of these shocks. Specifically, it seeks to address the following question: if an inflation targeting framework underpinned by a flexible exchange rate regime had not been in place, how would the economic contractions associated with these shocks have differed? Counterfactual simulations based on an estimated structural model indicate that countercyclical monetary policy and exchange rate flexibility added up to a total of 4 percentage points to real GDP growth during periods when Thailand had to weather these three major shocks.